Pertuzumab plus chemotherapy for platinum-resistant ovarian cancer: safety run-in results of the PENELOPE trial - González Martín, Antonio; Marmé, Frederik (International journal of gynecological cancer, 2016)
Objective In platinum-resistant ovarian cancer, adding pertuzumab to gemcitabine improved progression-free survival in the subgroup with low tumor HER3 messenger RNA expression. The 2-part PENELOPE trial (NCT01684878) is prospectively investigating pertuzumab plus chemotherapy in this population. - Patients and Methods Part 1 evaluated pertuzumab plus either topotecan or paclitaxel. Patients with platinum-refractory or platinum-resistant recurrent ovarian, primary peritoneal, or fallopian tube cancer and low HER3 messenger RNA expression (concentration ratio ≤2.81 by central quantitative reverse transcriptase-polymerase chain reaction testing on Cobas z480) received intravenous pertuzumab (840 mg loading dose then 420 mg every 3 weeks) with the investigator’s choice of topotecan (1.25 mg/m2 days 1-5 every 3 weeks) or weekly paclitaxel (80 mg/m2) until disease progression or unacceptable toxicity. The primary objective was to assess safety and tolerability. - Results Fifty patients were treated in part 1 (22 topotecan; 28 paclitaxel). In both cohorts, disease progression was the most common primary reason for discontinuing pertuzumab, and the most common all-grade adverse events (AEs) were fatigue/asthenia, anemia, and diarrhea. The most common grade ≥3 AEs were anemia (36%), neutropenia (27%), and fatigue/asthenia (18%) for topotecan, and peripheral sensory neuropathy (14%) and anemia (11%) for paclitaxel. Two patients receiving paclitaxel-pertuzumab died from AEs (abdominal infection; unexplained death). Median progression-free survival was 4.1 months (95% confidence interval, 1.9-6.1) with topotecan-pertuzumab and 4.2 months (95% confidence interval, 3.5-6.0) with paclitaxel-pertuzumab. - Conclusions Based on part 1 tolerability, the Independent Data Monitoring Committee had no objection to PENELOPE proceeding to part 2, a double-blind randomized comparison of chemotherapy (topotecan, paclitaxel, or gemcitabine) plus pertuzumab or placebo.